Impact of large-scale activities on macroscopic fundamental diagram: Field data analysis and modeling. (July 2022) - Niu, Xiao-Jing; Zhao, Xiao-Mei; Xie, Dong-Fan; Liu, Feng; Bi, Jun; Lu, Chaoru
Highlights: The impacts of large-scale activity on MFD are analyzed based on field data. The equilibria types and the stability are discussed based on nonlinear dynamic theory. A dynamic model is calibrated by field data to reveal real traffic state evolution. Some control strategies are designed based the calibrated model. Abstract: Large-scale activities always have serious impacts on regional traffic states. It is necessary for traffic planners to investigate the characteristics of network traffic flow under large-scale activities and apply proper management strategies. In this paper, based on the field data in Tianjin, China, the impact of large-scale activities and the corresponding control strategies on regional Macroscopic Fundamental Diagram (MFD) and regional traffic states are analyzed. The study area is divided into the inner area and the outer area. Based on the work of Haddad (2012) on the traffic perimeter control in two-region, a dynamic model is calibrated by the empirical data in Tianjin to study the influences of activities and control strategies. Based on the calibrated model, different control strategies are simulated to investigate the impacts on regional traffic flow. The results show that decreasing the transfer flow from the outer area will alleviate the congestion in the inner area effectively, and increasing the system outflow will reduce the densities of both two areas effectively. When the traffic states are already congested, the real control strategies cannot alleviate the congestion of the regional network effectively. According to the various impacts of different strategies, combined control strategies are proposed to mitigate the adverse impact of large-scale activities on the surrounding area.